Rainfall-yield relationships in rainfed sorghum in India - RAO, UMB; VIJAYALAKSHMI, K (MAUSAM, 1986)
The variation in rainfall and its distribution causes high fluctuations in production and productivity under rainfed agriculture. The data generated during last decade by All India co-ordinated Project for Dryland Agriculture were used for developing yield rainfall relationships. Total rainfall and its distribution affected the yield. Based on the correlations between yield and weekly rainfall from time of seeding, the growing season was divided into different periods. Various models were tried for prediction. The study was carried out for monsoon sorghum crop for four locations, viz., Hyderabad, Jhansi, Udaipur and Akola. Delayed seeding reduces the yield of sorghum. The crucial periods for rainfall are 8-10,6.12,3.6, 11.13 weeks for Hyderabad, Jhansi, Udaipur and Akola respectively. At Udaipur, high rainfall during 9-11 weeks reduces the yield possibly due to pollen wash and/or lodging. With the models tried, It IS possible to predict the yield of this crop with higher degree of predictability.